2013
DOI: 10.1136/gutjnl-2013-305130
|View full text |Cite
|
Sign up to set email alerts
|

A novel urine peptide biomarker-based algorithm for the prognosis of necrotising enterocolitis in human infants

Abstract: Objective Necrotising enterocolitis (NEC) is a major source of neonatal morbidity and mortality. The management of infants with NEC is currently complicated by our inability to accurately identify those at risk for progression of disease prior to the development of irreversible intestinal necrosis. We hypothesised that integrated analysis of clinical parameters in combination with urine peptide biomarkers would lead to improved prognostic accuracy in the NEC population. Design Infants under suspicion of havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Furthermore, a promising strategy in the identification of progressive NEC that requires surgical intervention has been formulated as a novel algorithm combining 27 clinical parameters and three urine fibrinogen peptide biomarkers, FGA1826, FGA1883 and FGA2659. This algorithm was reported to accurately predict the need for surgery in infants with suspected NEC in 100% of the cases analysed as opposed to only 40.1% when using the clinical parameters alone 49,50 , but it remains to be validated independently and in larger population studies. These and other biomarkers, therefore, could be considered for use in association with noninvasive monitoring techniques that assess intestinal tissue perfusion (for example, near-infrared spectroscopy) 51 to identify those infants at risk of developing NEC.…”
Section: Diagnosis Of Necmentioning
confidence: 99%
“…Furthermore, a promising strategy in the identification of progressive NEC that requires surgical intervention has been formulated as a novel algorithm combining 27 clinical parameters and three urine fibrinogen peptide biomarkers, FGA1826, FGA1883 and FGA2659. This algorithm was reported to accurately predict the need for surgery in infants with suspected NEC in 100% of the cases analysed as opposed to only 40.1% when using the clinical parameters alone 49,50 , but it remains to be validated independently and in larger population studies. These and other biomarkers, therefore, could be considered for use in association with noninvasive monitoring techniques that assess intestinal tissue perfusion (for example, near-infrared spectroscopy) 51 to identify those infants at risk of developing NEC.…”
Section: Diagnosis Of Necmentioning
confidence: 99%
“…The same group performed another study identifying three urinary coagulation cascade fibrinogen peptides that discriminated between medical and surgical NEC (AUC 0.86). When combined with clinical variables, these accurately predicted all infants requiring surgical intervention (65). Furthermore, they recently identified fibrinogen-γ dimers in plasma discriminated NEC (N=40) from sepsis (N=20), with an AUC 0.95.…”
Section: Proteomics and Metabolomics Applied To Necmentioning
confidence: 99%
“…Recently, biomarker discovery studies of the urinary proteome [16] and peptidome [17] have identified proteins and peptides associated with poor outcome (i.e., disease progression). Importantly, the biomarkers alone were not able to completely distinguish progressors from non-progressors, but were able to when clinical factors were incorporated into the prediction model.…”
Section: Improved Diagnostic Methodsmentioning
confidence: 99%